Understanding the Determinants of Health for People With Type 2 Diabetes - Maddigan, Sheri L. (© American Journal of Public Health 2006, 2006)
Objective. We assessed which of a broad range of determinants of health are most strongly associated with health-related quality of life (HRQL) among people with type 2 diabetes. Methods. Our analysis included respondents from the Canadian Community Health Survey Cycle 1.1 (2000–2001) who were aged 18 years and older and who were identified as having type 2 diabetes. We used regression analyses to assess the associations between the Health Utilities Index Mark 3 and determinants of health. Results. Comorbidities had the largest impact on HRQL, with stroke (−0.11; 95% confidence interval [CI] = −0.17, −0.06) and depression (−0.11; 95% CI = −0.15, −0.06) being associated with the largest deficits. Large differences in HRQL were observed for 2 markers of socioeconomic status: social assistance (−0.07; 95% CI=−0.12, −0.03) and food insecurity (−0.07; 95% CI=−0.10, −0.04). Stress, physical activity, and sense of belonging also were important determinants. Overall, 36% of the variance in the Health Utilities Index Mark 3 was explained. Conclusion. Social and environmental factors are important, but comorbidities have the largest impact on HRQL among people with type 2 diabetes.